PENGARUH BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA DALAM MENINGKATKAN KINERJA KARYAWAN (STUDI KASUS PT PLN (PERSERO) DISTRIBUSI JAKARTA RAYA) - Heri Purwanto (Journal of Economics and Business Aseanomics (JEBA), 2019)
The researcher aims to know how the influence of organizational culture and work motivation on job satisfaction with employee performance (Case Study of PT. STATEELECTRIC COMPANY (Persero) Distribution Jakarta Raya). Hypothesis used in this research: Organizational culture have an effect on to job satisfaction, work motivation influence tojob satisfaction, organizational culture influence to employee performance, work motivation influence to employee performance, job satisfaction influence to employee performance. The data were collected by using questionnaires distributed to respondents. The population in this study is 1780 employees, with sampling used in this study is probability sampling, with the technique of sample random sampling from the total of the existing population then thesample of the study of 327 respondents. Instrument calibration was performed to test the validity of grain and product moment and reliability was calculated using the coefficient ofcronbach's alpha. The hypothesis used in this research is to use the tenure of Structural Equation Model (SEM) analysis. The results of this study conclude that the organizationalculture variables affect the job satisfaction, while organizational culture affects the performance of the rich. It can be concluded that organizational culture and job satisfaction have an influence on employee performance. Motivation of work has an influence on job satisfaction, while work motivation has an influence on employee performance. It can be concluded that the motivation of work more influence on job satisfaction when compared to employee performance. Job satisfaction has an effect on employee performance. Overall, which has the most influence on employee performance is job satisfaction. Based on the results of these studies, in improving employee performance requires an individual attitude that is emotional to the job with job responsibilities.